2016
DOI: 10.1039/c6ra13159j
|View full text |Cite
|
Sign up to set email alerts
|

In situ identification of the molecular-scale interactions of phenol-formaldehyde resin and wood cell walls using infrared nanospectroscopy

Abstract: Atomic force microscope infrared spectroscopy (AFM-IR), contact resonance AFM (CR-AFM) measurement, and nanoindentation were combined to identify the interactions between wood cell wall and phenol-formaldehyde resin (PF) on the nanoscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…The intensity of the C=C stretching and C-O stretching at 1656 cm −1 , 1376 cm −1 , and 1336 cm −1 decreased significantly, while some new bands at 1287 cm −1 and 778 cm −1 appeared as compared to the control cell wall, which can be attributed to the penetration of PF resin into the cell wall [33,34]. Moreover, a relatively broader band between 1150 cm −1 and 1100 cm −1 appeared in the spectra of modified wood, corresponding to the asymmetric stretching vibration of C-O-C aliphatic ether, which is in agreement with the literature that the chemical reactions of the -OH groups of wood and PF resin occurred at the cell wall level [35,36]. appeared as compared to the control cell wall, which can be attributed to the penetration of PF resin into the cell wall [33,34].…”
Section: Local Chemical Analysis By Ramansupporting
confidence: 88%
“…The intensity of the C=C stretching and C-O stretching at 1656 cm −1 , 1376 cm −1 , and 1336 cm −1 decreased significantly, while some new bands at 1287 cm −1 and 778 cm −1 appeared as compared to the control cell wall, which can be attributed to the penetration of PF resin into the cell wall [33,34]. Moreover, a relatively broader band between 1150 cm −1 and 1100 cm −1 appeared in the spectra of modified wood, corresponding to the asymmetric stretching vibration of C-O-C aliphatic ether, which is in agreement with the literature that the chemical reactions of the -OH groups of wood and PF resin occurred at the cell wall level [35,36]. appeared as compared to the control cell wall, which can be attributed to the penetration of PF resin into the cell wall [33,34].…”
Section: Local Chemical Analysis By Ramansupporting
confidence: 88%
“…There are few reports about plant cell wall chemistry at the nanoscale without using any form of extraction or special treatment. The techniques used in these studies are based on IR spectroscopy, either using AFM-IR (Wang et al, 2016) or an analogous technique, such as photonic-nanomechanical force microscopy (Tetard et al, 2015;Farahi et al, 2017). Wang et al (2016) accurately measured the penetration of resin in the cell wall using AFM-IR.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques used in these studies are based on IR spectroscopy, either using AFM-IR (Wang et al, 2016) or an analogous technique, such as photonic-nanomechanical force microscopy (Tetard et al, 2015;Farahi et al, 2017). Wang et al (2016) accurately measured the penetration of resin in the cell wall using AFM-IR. Tetard et al (2015) and Farahi et al (2017) also identified nanoscale compositional changes of lignin and cellulose dominance in the cell wall after treatments with extractives based on photonic-nanomechanical force microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an obvious drawback which needs to be overcome when these resins used. [59] PF (phenol-formaldehyde) resins and their reinforced materials can also resist harsh thermal conditions, they can be used as carbon-mineral materials by blending with other substances and they also have other applications [60][61][62] ; however, researchers should also consider their adhesive and toughness properties during applications.…”
Section: Farid Bakir Is Professor At Arts Et Métiers Paristech Andmentioning
confidence: 99%